Gender: A key dimension linking agricultural programs to improved nutrition and health - Meinzen-Dick, Ruth S.; Behrman, Julia A.; Menon, Purnima; Quisumbing, Agnes R. (International Food Policy Research Institute, 2011)
Improving the livelihoods and well-being of the rural poor is an important aim of agricultural development, promoted through agricultural intensification and commercialization strategies. But improved agricultural productivity does not necessarily translate into improved health and nutrition, either for producers or consumers. How can standard agricultural development strategies—promoting agricultural intensification, greater linkages to markets, and high-value production—also create positive impacts on health and nutrition? This brief argues that a key element linking these programs to improved outcomes is the dimension of gender roles and gender equity.